Experimental Use of Microwaves in the High Temperature Foaming Process of Glass Waste to Manufacture Heat Insulating Material in Building Construction - Lucian Paunescu; Sorin Mircea Axinte; Marius Florin Dragoescu; Felicia Cosmulescu (Newinera Publisher, 2020)
Abstract The aim of the paper was the experimental manufacture of cellular glass from glass waste and coal ash as raw material and silicon carbide as a foaming agent, using the unconventional microwave heating technique. This heating technique, although known since the last century and recognized worldwide as fast and economical, is not yet industrially applied in high temperature thermal processes. The cellular glass manufacturing process requires high temperatures and the use of microwaves in this process is the originality of the work. The experiments aimed at producing thermal insulating materials with high porosity and low thermal conductivity for building construction similar in terms of quality to those manufactured industrially by conventional techniques, but with lower energy consumption. The obtained samples had adequate characteristics (apparent density 0.22-0.32 g/cm3, porosity 85.5-90.0%, thermal conductivity 0.043-0.060 W/m·K, compressive strength 1.23-1.34 MPa), and the specific energy consumption was low (0.84-0.89 kWh/kg). Theoretically, given the use of microwave equipment on an industrial scale, this consumption comparable in value to that industrially achieved by conventional techniques could decrease by up to 25%.